2017
DOI: 10.1039/c7ee01931a
|View full text |Cite
|
Sign up to set email alerts
|

Engineering interface structures between lead halide perovskite and copper phthalocyanine for efficient and stable perovskite solar cells

Abstract: CuPC-applied perovskite solar cells show excellent long-term thermal stability which is attributed to the reliable interface and intrinsic heat-resistance of CuPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
151
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(157 citation statements)
references
References 43 publications
4
151
0
Order By: Relevance
“…Although2 ,2',7,7'-tetrakis[N,N-bis(p-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) are standard choicesf or HTMs in high-performance PSCs, [15][16][17] the PCEs of these PSCs decrease drastically under high-temperature conditions because of the low phase-transition temperatures of the HTMs. [18,19] Research efforts have therefore been directed towards finding solution-processable HTMs possessingn ot only suitable energy levels for efficient hole extraction but also high thermal durability for industrial processes. [14,20,21] HTMs containing polycyclic aromatic skeletons, such as truxene, [22,23] triazatruxene, [24,25] benzotrithiophene, [26] or thiolated nanographene, [27] as the central core attachedt oa rylamine derivatives have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Although2 ,2',7,7'-tetrakis[N,N-bis(p-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) are standard choicesf or HTMs in high-performance PSCs, [15][16][17] the PCEs of these PSCs decrease drastically under high-temperature conditions because of the low phase-transition temperatures of the HTMs. [18,19] Research efforts have therefore been directed towards finding solution-processable HTMs possessingn ot only suitable energy levels for efficient hole extraction but also high thermal durability for industrial processes. [14,20,21] HTMs containing polycyclic aromatic skeletons, such as truxene, [22,23] triazatruxene, [24,25] benzotrithiophene, [26] or thiolated nanographene, [27] as the central core attachedt oa rylamine derivatives have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been focused toward avoiding the degradation of the solar cells by, for example by modifying the perovskite active layer and by employing encapsulating layers . In this context it was also shown that engineering the interface between the perovskites and the charge transport layers increases the lifetime of the photovoltaic devices . Hence interfacial engineering can have beneficial effects on both charge transport and stability of the halide perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between ETHH NP arrays and perovskite was explored by photovoltage spectroscopy and simulated extinction spectrum. For the region from 350 to 600 nm, we found that the ETHH NP arrays, as a hole transport layer, improved the plasmonic hot‐electron injection efficiency from the ETHH NP arrays into the perovskite film after excitation of the Au plasmon band, inducing higher photovoltage and detectable blue shift as band structures of metal/semiconductor contact (Figure d,e) . For the spectra between 600 and 950 nm, ETHH NP arrays covered by perovskite film exhibited multipeak spectra due to quantization of angular momenta.…”
mentioning
confidence: 86%